Understanding physics - Cassidy, David; Holton, Gerald; Rutherford, James (New York, Springer, 2002)
A thorough grounding in contemporary physics while placing the subject into its social and historical context. Based largely on the highly respected Project Physics Course developed by two of the authors, it also integrates the results of recent pedagogical research. The text thus teaches the basic phenomena in the physical world and the concepts developed to explain them; shows that science is a rational human endeavour with a long and continuing tradition, involving many different cultures and people; develops facility in critical thinking, reasoned argumentation, evaluation of evidence, mathematical modelling, and ethical values. The treatment emphasises not only what we know but also how we know it, why we believe it, and what effects this knowledge has.
Illustration credits 819-828p.; Index 829-851p.
Keywords: Physics; General Science